Investigation of vibrofluidized granular layer modes using OpenFOAM - Orlova, N.S.; Kachalkina, Ya.N. (Trudy Instituta sistemnogo programmirovaniâ, 2018)
Vibrofluidization is widely used in various industrial processes. So the study of vibrofluidization modes is current research. In this paper we investigated the modes of vibrofluidized layer using the package OpenFOAM. The results of modelling of the vibrofluidized layer dynamics at different values of the amplitude and frequency of oscillations, the thickness of the filling, were presented. The modes in which layer becomes unstable were identified. Wavelets formed from granular material and the jetting channels appear in these modes